Reactive oxygen species in spermatozoa: methods for monitoring and significance for the origins of genetic disease and infertility - Aitken R John; Baker Mark A (BMC, 2005)
Abstract Human spermatozoa generate low levels of reactive oxygen species in order to stimulate key events, such as tyrosine phosphorylation, associated with sperm capacitation. However, if the generation of these potentially pernicious oxygen metabolites becomes elevated for any reason, spermatozoa possess a limited capacity to protect themselves from oxidative stress. As a consequence, exposure of human spermatozoa to intrinsically- or extrinsically- generated reactive oxygen intermediates can result in a state of oxidative stress characterized by peroxidative damage to the sperm plasma membrane and DNA damage to the mitochondrial and nuclear genomes. Oxidative stress in the male germ line is associated with poor fertilization rates, impaired embryonic development, high levels of abortion and increased morbidity in the offspring, including childhood cancer. In this review, we consider the possible origins of oxidative damage to human spermatozoa and reflect on the important contribution such stress might make to the origins of genetic disease in our species.